Harmony Gaze Framework dalam Pengembangan Desa Wisata Latimojong - Pramadika, Taukhid; Malihah, Elly; Andari, Rini (Politeknik Pariwisata NHI Bandung, 2025)
This study explores the relationship and interaction between the tourist gaze and local people gaze in the development of Latimojong Tourism Village, Enrekang Regency. With its natural beauty and rich cultural heritage, the village holds significant potential as a community-based tourism destination. However, the primary challenge lies in ensuring harmony between tourist expectations and the needs of the local community. This research adopts a qualitative approach through in-depth interviews, field observations, and literature analysis. The findings reveal that the tourist gaze, which reflects tourists' perceptions of cultural authenticity and unique experiences, often conflicts with the local community’s perspectives, which prioritize environmental preservation, cultural traditions, and community welfare. To address this issue, the Harmony Gaze Framework was developed, encompassing perspective dialogue, collaborative tourism activities, shared value mapping, and participatory evaluation. This concept aims to establish an inclusive, sustainable, and community-based tourism management model. The implementation of this framework is expected to optimize the tourist appeal of Latimojong Village without compromising its local identity while simultaneously providing economic and social benefits for the community. Thus, Latimojong Tourism Village can serve as a model for community-based tourism development that is adaptive to contemporary changes and advancements.